Acute Stress in Health Workers in Colombia 2017-2021: A Cross-Sectional Study - Mery Gonzalez Delgado; Jesus David Cortes Gil; Deysy Lisette Rodriguez Araujo; Jose Joaquin Mira Solves; Erika Bibiana Rodriguez Gallo; Alejandra Salcedo Monsalve; Luz Angela Arrieta Arteta; Carolina del Pilar Villalba Toquica; Juan Carlos Morales Ruiz (Frontiers Media S.A., 2023)
Objectives: Analyze the presence of acute stress response after adverse events in human talent in Colombian health institutions from 2017 to 2021.Methods: Cross-sectional study of prevalence, carried out on 838 members of the human talent in health (professionals, technicians, technologists, and auxiliaries) of Colombian health institutions in the study period with the application of the EASE instrument. Univariate analysis using descriptive statistical techniques, chi-square and Student's t-test, and bivariate analysis with a Poisson regression model using the institucional SPSS v. 26.Results: The prevalence of adverse events in the last 5 years was 33.8%, presenting levels of acute stress qualifying as Medium-high emotional overload at 21.91%, while extreme acute stress was at 3.53%. The prevalence of risk for presenting acute stress after being involved in an adverse event was PR: 1.30 (CI: 1.24-1.36).Conclusion: Acute stress in human talent after adverse events is limiting health and care capacity and must be efficiently addressed by health institutions. Psychosocial risk is linked within the framework of the patient safety program and the institutional occupational health and safety management systems.